Degradation of Trichloroethylene Contaminated Soil by Zero-Valent Iron Nanoparticles. (14th October 2012) - Ibrahem, Amira Kamal; Abdel Moghny, Thanaa; Mustafa, Yasser Mohamed; Maysour, Nermine Elsyed; Mohamed Saad El Din El Dars, Farida; Farouk Hassan, Reham
Abstract : Trichloroethylene (TCE) contaminated soil has received extensive attention in the environmental issues. Nanoscale zero-valent iron (NZVI) is considered as an excellent reduction catalyst due to fast degradation of chlorinated solvents. Therefore, this paper aims to evaluate TCE removal from soil by surfactant modified nanoscale zero-valent iron (SNZVI). In this respect, fixed 500 g soil having a diameter range 0.5–1 mm was polluted with 10 mL TCE and put inside glass column of 2.5 cm diameter × 300 cm length. The NZVI solution was prepared from reduction of FeCL3 by NaBH4 and coating with 2.5 g nonionic surfactant (Tween 85) to produce iron nanoparticle concentration of 0.1 g/L. The prepared iron nanoparticle was poured into contaminated soil and left to stir at a constant rate for 24 days. The reductive dechlorination of TCE was measured as a function of increasing chloride ion. It was found that the TCE dechlorination in the presence of iron surfaces displayed pseudo first-order kinetics. The TCE degradation rate constant (K obs ) is4 × 10 − 4 h − 1 . Also, about 30% of TCE was removed within initial 6 days. The obtained specific rate constant (K SA ) was6.081 × 10 − 4 L · h − 1 · m − 2 and is lower than other studies carried into aqueous phase by about 23 orders of magnitude. Finally, the SNZVI was found to be effective and fully removed to TCE within 456 hours.